Hallmarks of pluripotency - De Los Angeles, Alejandro; Ferrari, Francesco; Xi, Ruibin; Fujiwara, Yuko; Benvenisty, Nissim; Deng, Hongkui; Hochedlinger, Konrad; Jaenisch, Rudolf; Lee, Soohyun; Leitch, Harry G.; Lensch, M. William; Lujan, Ernesto; et al. (Nature (London), 2015)
In response to the need for a defined set of criteria to assess stem-cell potency, this review proposes guidelines for the evaluation of newly derived pluripotent stem cells, from functional assays to integrative molecular analyses of transcriptional, epigenetic and metabolic states. Defining pluripotency Pluripotent stem cells have the capacity to produce all the cell types of an organism. Pluripotent stem cells were recently shown to exist in different states, during development or when obtained via distinct programming methods. These reports highlight the need for a defined set of criteria to assess stem cell potency. This review proposes guidelines for the evaluation of newly derived pluripotent stem cells, from functional assays to integrative molecular analyses of transcriptional, epigenetic and metabolic states. Stem cells self-renew and generate specialized progeny through differentiation, but vary in the range of cells and tissues they generate, a property called developmental potency. Pluripotent stem cells produce all cells of an organism, while multipotent or unipotent stem cells regenerate only specific lineages or tissues. Defining stem-cell potency relies upon functional assays and diagnostic transcriptional, epigenetic and metabolic states. Here we describe functional and molecular hallmarks of pluripotent stem cells, propose a checklist for their evaluation, and illustrate how forensic genomics can validate their provenance.